Relevansi Adab Penuntut Ilmu pada Era Digital Perspektif Kitab Ta’lim Muta’allim - Alim Putra Budiman; Fathor Rohim; Fahrudin Mukhlis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This article describes the relevance of the ethics of students in the Ta'lim Muta'allim book to the ethics of students in the digital era. But with these conveniences, are conventional methods no longer relevant for learning today. The author uses a conventional literature review method reading and reviewing relevant books and articles as research support, the author's data collection uses the documentation method and the results of data collection are analyzed using content analysis techniques. The results of this study produce an explanation of the relevance of ethics of students to the digital era from the perspective of 13 chapters of the Ta'lim Muta'allim book. It was found that there is a relevance of the values of the Ta'lim Muta'allim book, what has changed is the method and practice in implementing the values of the Ta'lim Muta'allim book. Differences in methods and times do not change the entity of good values in the ethics of students even though the century and era have changed, only different perspectives in how to practice it.